Pengaruh Penataan Produk terhadap Keputusan Pembelian Konsumen di Alfamidi Jl.Tuasan - Dwi Rahmadani; Anindia Jovita Br Ginting; Yulie Aisyah Binrany; Azahra Salwa Amani; Ivo Selvia Agusti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of product arrangement on consumer purchasing decisions at Alfamidi Jl. Tuasan, Medan. Product arrangement is a crucial visual merchandising strategy in the modern retail industry to attract consumer attention and increase sales. The study used a quantitative approach with an associative method, involving 30 respondents selected through accidental sampling techniques. Data were collected using a questionnaire with a 5-point Likert scale and analyzed using simple linear regression with the help of SPSS version 25. The results showed that product arrangement had a positive and significant effect on consumer purchasing decisions with a coefficient of determination (R²) of 90.2%. The regression equation Y = 1.245 + 0.675X shows that every one unit increase in product arrangement will increase purchasing decisions by 0.675 units. The t-test produced a calculated t value of 16.071> t table 2.048 with a significance of 0.000 <0.05, confirming the research hypothesis. This finding confirms that product layout elements such as ease of access, visual appeal, and layout comfort play a vital role in influencing consumer behavior and increasing the effectiveness of retail marketing strategies.